Writing to the World : Letters and the Origins of Modern Print Genres - King, Rachael Scarborough (Book collections on Project MUSE., 2018)
In Writing to the World, Rachael Scarborough King examines the shift from manuscript to print media culture in the long eighteenth century. She introduces the concept of the "bridge genre," which enables such change by transferring existing textual conventions to emerging modes of composition and circulation. She draws on this concept to reveal how four crucial genres that emerged during this time--the newspaper, the periodical, the novel, and the biography--were united by their reliance on letters to accustom readers to these new forms of print media. King explains that as newspapers, scientific journals, book reviews, and other new genres began to circulate widely, much of their form and content was borrowed from letters, allowing for easier access to these unfamiliar modes of printing and reading texts. Arguing that bridge genres encouraged people to see themselves as connected by networks of communication--as members of what they called "the world" of writing--King combines techniques of genre theory with archival research and literary interpretation, analyzing canonical works such as Addison and Steele's Spectator, Samuel Johnson's Lives of the Poets, and Jane Austen's Northanger Abbey alongside anonymous periodicals and the letters of middle-class housewives. This original and groundbreaking work in media and literary history offers a model for the process of genre formation. Ultimately, Writing to the World is a sophisticated look at the intersection of print and the public sphere.